Dogma of christ - "Fromm, Erich" (London, 2004)
When he was 26, the great psychoanalyst and philosopher Erich Fromm abandoned Judaism, though he himself was descended from a long line of rabbis and the product of a devout Jewish upbringing. The title essay of this collection was first published in 1930, just four years after he made that first, decisive split. It was to point towards the future Fromm's work, presenting the view that an understanding of basic human needs is essential to the understanding of society and mankind itself. The following essays too, show a man who would eventually establish himself as a major thinker, producing some of that era's most influential and astute political works.
Keywords: Psychology